Characteristics of facial nerve palsy during childhood in Japan: frequency of varicella-zoster virus association - OGITA, SATOKO; TERADA, KIHEI; NIIZUMA, TAKAHIRO; KOSAKA, YASUKO; KATAOKA, NAOKI (Pediatrics international, 2006)
Background: The aim of this study was to clarify the clinical characteristics of facial nerve palsy and the frequency of varicella–zoster virus association in Japanese children, retrospectively. Methods: The subjects were 30 facial nerve palsy patients less than 15 years old, treated in the Department of Pediatrics, Kawasaki Medical School Hospital, Okayama, Japan, during the last 10 years. Results: The male/female and right/left ratios were 16/14 and 16/13, respectively. The patients included 21 cases (70%) of Bell’s palsy, four cases (13%) due to otitis media, three cases (10%) of Ramsay Hunt syndrome and two cases (7%) due to birth trauma. There were six cases of zoster sine herpete among the Bell’s palsy cases. Conclusion: Varicella–zoster virus‐associated facial palsy was found in nine (36%) of the 25 patients examined. Zoster sine herpete was more frequently encountered in children than adults. Ramsay Hunt syndrome was found in school‐age children and zoster sine herpete was often found in preschool children. The period of recovery was fast for facial nerve palsy due to acute otitis media, which occurred within 23 months of age, after myringotomy and administration of antibiotics.